KAJIAN KUALITAS AIR DAN STATUS MUTU AIR SUNGAI METRO DI KECAMATAN SUKUN KOTA MALANG - Azwar Ali (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstractMetro River is utilized by society who lives along the river in order to fulfill their dailyneeds, such as public bathing, washing, and toilet facilities, irrigation for agriculture,disposal for garbage and water domestic waste, the use of water would reduce water qualityof the river. Objectives of the research were to find out and analyze condition of waterquality of the river and water quality status in Metro River, as well as its suitability to waterquality standard according to its purpose. Determination of the sample-collecting spotshas applied purposive sampling method, while water sample has been taken using grabsample method. Water quality analysis used the prevailing standard method and waterquality status was determined by Pollution Index method. Result of the research showedthat water quality in Metro River, for DO parameter in station 3, was below the qualitystandard according to its purpose and for BOD parameter in station 2 and 3, it was beyondthe standard of water quality according to its purpose, for class III. Meanwhile, quality ofwater in Metro River from upstream to the downstream has been decreasing as shown by theincreasing value of PI, water quality status in station 1 and 2 showed “excellent condition”,and the station 3 showed “mild polluted”.